Atazanavir–bilirubin interaction: a pharmacokinetic–pharmacodynamic model - Lozano R; Domeque N; Apesteguia AF (Clinical Pharmacology: Advances and Applications, 2013)
Roberto Lozano,1 Nieves Domeque,2 Alberto-Fermin Apesteguia3 1Pharmacy Department, 2Psychiatry Department, Hospital Real Nuestra Señora de Gracia, 3Pharmacy Department, Hospital Clinico Universitario "Lozano Blesa", Zaragoza, Spain Purpose: The aim of this work was to analyze the atazanavir–bilirubin relationship, using a new mathematical approach to pharmacokinetic–pharmacodynamic models, for competitive drug interactions based on Michaelis–Menten equations. Patients and methods: Because atazanavir induces an increase of plasma bilirubin levels, in a concentration-dependent manner, we developed a mathematical model, based on increments of atazanavir and bilirubin concentrations at steady state, in HIV infected (HIV+) patients, and plotted the corresponding nomogram for detecting suboptimal atazanavir exposure. Results: By applying the obtained model, the results indicate that an absolute value or an increment of bilirubin at steady state below 3.8 µmol/L, are predictive of suboptimal atazanavir exposure and therapeutic failure. Conclusion: We have successfully implemented a new mathematical approach to pharmacokinetic–pharmacodynamic model for atazanavir–bilirubin interaction. As a result, we found that bilirubin plasma levels constitute a good marker of exposure to atazanavir and of viral suppression. Keywords: atazanavir, bilirubin, HIV/AIDS, pharmacodynamics, pharmacokinetics